ANALISIS STRATEGI BERSAING TOKO ROTI X BERDASARKAN IE- MATRIKS - Ade Putra Halomoan Siregar (Jurnal Administrasi Bisnis, 2020)
The bakery industry is one of the contributors to economic growth in the food and beverage industry sector. The growth of the bakery industry is influenced by changes in urban lifestyles where people are now accustomed to consuming bakery products for breakfast, to eat with coffee and so forth. PT. X is a bakery company that was founded in 2004 and is located in Bandung City. The increase in demand for bakery products has influenced this company to better understand its company's position so that it can determine the right strategy going forward to compete with competitors.This research uses a case study method. The data analysis technique uses PESTEL analysis, Porter's 5 Forces, Internal Environmental Analysis which will then be calculated by IFE & EFE Matrix to determine the company's position.The results showed that at this time PT.X is in quadrant I in IE Matrix. This shows that the influence of strengths and weaknesses has a greater influence on business activities and production. Therefore, the most appropriate strategy to use is an intensive strategy or integration strategy.Keywords: Competitive Business Strategy, SWOT Analysis, Bakery Industry